23-Gauge vitrectomy with external drainage therapy as a novel procedure to displace massive submacular hemorrhage secondary to polypoidal choroidal vasculopathy. Issue 32 (August 2016) - Liu, Hui; Zhang, Lu-yi; Li, Xiao-xia; Wu, Miao-qin
Abstract: Introduction: Massive subretinal hemorrhage (SRH) due to polypoidal choroidal vasculopathy (PCV) remains a challenging field and the best treatment is still not certain. In the present study, we performed a novel surgical method which combined 23-gauge vitrectomy with external drainage therapy for displace massive SRH secondary to PCV. Methods: From April 2015 to July 2015, 4 consecutive patients with massive SRH secondary to PCV received 23-gauge transconjunctival sutureless vitrectomy with external drainage therapy. Massive SRH was drained by scleral tunnel which was created using 30-gauge ultrathin needles during vitrectomy. We assessed the feasibility and safety of this procedure by analyzing best-corrected vision acuity (BCVA), central foveal thickness (CFT), and complication. Results: Four patients had a mean age of 63.8 ± 6.4 years (range: 59–73 years). The average interval between onset of symptoms of SRH and surgery was 23.8 ± 11.1 days (range: 10–35 days). Mean follow-up duration was 7.0 ± 0.8 months. All patients completed 6 months follow-up. Mean BCVA gradually improved during the follow-up period. At 6 months after treatment, mean BCVA was significantly improved in comparison to preoperative findings ( P = 0.043, paired t test). One month after treatment, mean CFT was significantly thinner than baseline ( P = 0.002, paired t test). No serious ocular or systemic adverse events were observed to be associated with combination of 23-gauge vitrectomy with external drainage therapy during the 6 months follow-up period. Conclusions: Our results show that a combination of 23-gauge vitrectomy with external drainage therapy is a novel effective and safe procedure that may be a good alternative for massive SRH due to PCV.